Implementasi Flashcard Motion-Based dalam PAI untuk Meningkatkan Kemampuan Afektif Peduli Lingkungan pada Siswa ABK - Nur Laila Novitasari; Irma Soraya; Mohammad Kurjum (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: Islamic Religious Education aims to shape students' character, including fostering environmental care attitudes, yet traditional methods are often less effective for students with special needs (ABK) who require tailored approaches. This study evaluates the implementation of motion-based flashcards in Islamic Religious Education to enhance the affective abilities of ABK students concerning environmental care. Employing a literature review method, data were systematically collected from books, journals, and scholarly articles, focusing on Krathwohl’s affective domain theory, Gardner’s Multiple Intelligences theory, characteristics of ABK, and the effectiveness of flashcard media. Data collection utilized a literature review checklist to record key information and a data categorization matrix to organize findings, with inclusion criteria encompassing relevance, recency (published within the last 10 years, except for classical theories), and source credibility, while excluding irrelevant or less credible literature. Data were analyzed using a qualitative-descriptive approach. Findings indicate that motion-based flashcards enhance motivation and internalization of environmental care values among ABK students, despite challenges such as varying motor skills and limited facilities. With adaptations, motion-based flashcards hold potential as an effective inclusive strategy in Islamic Religious Education.Abstrak: Pendidikan Agama Islam bertujuan membentuk karakter siswa, termasuk sikap peduli lingkungan, namun metode tradisional kurang efektif bagi siswa berkebutuhan khusus (ABK) yang memerlukan pendekatan khusus. Penelitian ini mengevaluasi implementasi flashcard motion-based dalam Pendidikan Agama Islam untuk meningkatkan kemampuan afektif siswa ABK terkait peduli lingkungan. Menggunakan metode studi pustaka, data dikumpulkan dari buku, jurnal, dan artikel, dengan fokus pada teori ranah afektif Krathwohl, teori Multiple Intelligences Gardner, karakteristik ABK, dan efektivitas flashcard. Pengumpulan data dilakukan sistematis menggunakan lembar telaah pustaka dan matriks pencatatan, dengan kriteria inklusi berupa relevansi, aktualitas (10 tahun terakhir, kecuali teori klasik), dan kredibilitas sumber, serta eksklusi untuk literatur tidak relevan. Data dianalisis secara kualitatif-deskriptif. Hasil menunjukkan flashcard motion-based meningkatkan motivasi dan internalisasi nilai peduli lingkungan, meskipun tantangan seperti variasi kemampuan motorik dan keterbatasan fasilitas menghambat. Dengan adaptasi, flashcard motion-based berpotensi menjadi strategi inklusif efektif dalam PAI.